Frequency and type of synthetic cannabinoids analyzed in the council of forensic medicine istanbul narcotic department Turkey - GÜLHAN, REZZAN (My University, 2011)
Objectives: In recent years, synthetic cannabinoids are frequently observed in seized materials all over the world. These new generation designer drugs, also known as “Spice” or “Legal Highs,” can easily be obtained via the internet and are in sold mixed with herbal substances. In this study, we aimed to evaluate the type and detection frequency of synthetic cannabinoids sent to be analyzed in our laboratory over a 10-month period between August 2010 and April 2011. Materials and methods: Herbal materials sent by judicial authorities to The Council of Forensic Medicine-Istanbul Narcotic Department between August 2010 and April 2011, were analyzed in the study. All materials were analyzed by physical examination, thin layer chromatography and GC-MS (Agilent 6890GC/5973MS inert, with 30m HP-5MS column). Results: A total of 1171 herbal substances were analyzed during the 10-month investigation period and 1156 of them (98.7%) contained synthetic cannabinoids. We found both JWH-018 and JWH-081 in 760 (65.7%) samples out of 1156; JWH-018 alone in 382 (33%); CP47,497 (C8) in 5 (0.4%); both CP47,497 (C8) and JWH-018 in 7 (0.6%) samples; JWH-250 alone in 2 (0.2%) samples. Samples material had different package names such as “Bonzai Aromatic Potpori” (n=755), “Bonzai” (n=313), “Heaven” (n=14), “Aromatic Incense,” (n=6), “Yukatan Fire” (n=7), “Tribal Warrior Ultimate” (n=5), “Jamaican Gold” (n=43) and “Jamaican Sprit” (n=5). All Bonzai packages (n=313) contained JWH-018 while 2 samples contained JWH-250. JWH-018 along with JWH-081 was detected in “Bonzai Aromatic Potpori” (n=755) and in “Jamaican Spirit” (n=5). All “Yukatan Fire” packages contained JWH-018 with CP47,497 (C8). “Tribal Warrior Ultimate” packages had CP47,497(C8) (n=5). The rest of packages with different names had JWH-018. Conclusions: JWH-018 was the most frequent type of synthetic cannabinoids (detected in 98.7% of 1156 samples). “Bonzai” and “Bonzai Aromatic Potpori” were the most common product name amongst the herbal products sent to our laboratory (n=1068). Although some of these synthetic cannabinoid compounds are banned by law, there is not an “analogue or derivative” clause established in Turkey yet. The increase use of different derivatives, lack of analytical data and reference standards for analysis, lack of information on metabolism and metabolites for toxicological analysis in human subjects are important problems that need to be solved.
Keywords: Synthetic Cannabinoids; JWH; Spice; Bonzai